(untitled) (MAUSAM, 1992)
Diurnal variability of surface wind speed, net heat exchange, sea surface temperature, vertical thermal structure and heat content at three locations, viz., station A (17° 59’N, 83° 53.9’E), station B (17° OO’N , 82° 32.1’E) and station C (16° 31..3’ N, 82° 21..8’E) off central east coast of India is described making use of the data collected on board R.V. Gaveshani during April 1989 .